What Does Equity Sector Orderflow Tell Us About the Economy? - Beber, Alessandro; Brandt, Michael W.; Kavajecz, Kenneth A. (Review of Financial Studies, 2011)
Investors rebalance their portfolios as their views about expected returns and risk change. We use empirical measures of portfolio rebalancing to back out investors' views, specifically, their views about the state of the economy. We show that aggregate portfolio rebalancing across equity sectors is consistent with sector rotation, an investment strategy that exploits perceived differences in the relative performance of sectors at different stages of the business cycle. The empirical footprint of sector rotation has predictive power for the evolution of the economy and future bond market returns, even after controlling for relative sector returns. Contrary to many theories of price formation, trading activity, therefore, contains information that is not entirely revealed by resulting relative price changes. The Author 2011. Published by Oxford University Press on behalf of The Society for Financial Studies. All rights reserved. For Permissions, please e-mail: journals.permissions@oup.com., Oxford University Press.